2022
DOI: 10.1021/acs.est.1c05635
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Heterotrophic Methylmercury Detoxifying Bacteria across Oceanic Regions

Abstract: Microbial reduction of inorganic divalent mercury (Hg2+) and methylmercury (MeHg) demethylation is performed by the mer operon, specifically by merA and merB genes, respectively, but little is known about the mercury tolerance capacity of marine microorganisms and its prevalence in the ocean. Here, combining culture-dependent analyses with metagenomic and metatranscriptomic data, we show that marine bacteria that encode mer genes are widespread and active in the global ocean. We explored the distribution of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
(111 reference statements)
1
3
0
Order By: Relevance
“…Sphingobacteriales (Bacteroidetes) and Clostridiales (Firmicutes) were only detected in the merB sequence variants suggesting that some prokaryotes could potentially present only the merB gene as recently reported . Like for merA genes, all the merB -containing taxonomic groups detected in our study were previously described as merB -coding bacteria, ,, and Alteromonadales include members that have been experimentally proven in the laboratory to be able to degrade MeHg at reasonably high concentrations . Once again, the absence of archaeal sequences was observed among the merB genes, and similar factors explained for the merA gene detection may account for the absence of merB sequences.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Sphingobacteriales (Bacteroidetes) and Clostridiales (Firmicutes) were only detected in the merB sequence variants suggesting that some prokaryotes could potentially present only the merB gene as recently reported . Like for merA genes, all the merB -containing taxonomic groups detected in our study were previously described as merB -coding bacteria, ,, and Alteromonadales include members that have been experimentally proven in the laboratory to be able to degrade MeHg at reasonably high concentrations . Once again, the absence of archaeal sequences was observed among the merB genes, and similar factors explained for the merA gene detection may account for the absence of merB sequences.…”
Section: Resultssupporting
confidence: 80%
“…However, a recent study reported that merA and merB of Alteromonas and Marinobacter spp. bacterial isolates, capable of demethylating MeHg and reducing Hg II forms, were widespread in surface, the deep chlorophyll maximum, and mesopelagic waters of different oceanographic regions, 47 suggesting the relevance of these processes, although rarely reported. Nevertheless, the global diversity, biogeography, activity, and especially the environmental drivers of the microorganisms involved in Hg II reduction and MeHg demethylation in the bathypelagic realm remain largely unknown.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another highly cosmopolitan sequence in terms of carrier genus is the well-known alkylmercury lyase sequence, also known as the mer B gene, which encodes an enzyme that degrades the highly toxic methyl-Hg form into lesser toxic ones. A recent study shows that mercury resistance genes are widely distributed in the marine realm [ 58 ]. Nevertheless, it is also known that its abundance responds to pollution gradients [ 59 ] and, therefore, considering its ubiquity, this resistome sequence can also provide a good candidate biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…From a different perspective, marine microorganisms possess unique properties owing to the need to adapt to disadvantageous environmental conditions caused by ions, such as alkaline and acidic water, and high osmotic stress. For example, microorganisms can change the valence, existence form, and solubility of the ion (Beam et al, 2018;Vigliaturo et al, 2020;Sanz-Saez et al, 2022;van de Velde et al, 2022).…”
Section: Introductionmentioning
confidence: 99%